The effects of hotel’s brand personality dimensions on customer’s satisfaction in Kuala Lumpur hotels / Nadiah Abu Zaireen - Abu Zaireen, Nadiah (2013)
Personality dimensions, namely, sincerity, excitement, competence, sophistication and ruggedness (Aaker, 1997), are applied to brands of products. It is the aim of this study to apply the same dimensions on hotel brands as to test whether the dimensions would reflect the hotel’s personality and eventually impacted on customers’ satisfaction. Using a quantitative approach, the data gathered through questionnaires which were distributed to the guests of five-star hotels in Kuala Lumpur. Descriptive statistics, correlation and regression analysis were used to analyze the data. From the five dimensions, sincerity had higher scores and it is the most influential dimension. As for ruggedness dimension, it has the no influence at all towards the customer satisfaction. It is also believed that brand personality is adaptable to hotel brands in the Malaysian context. From this study, the hospitality industry will have a better understanding of the brand personality of their hotel and its relationship to customers’ satisfaction. For future research, it is hope to test hotels in different states in Malaysia and also other category of lodging in other developing countries.